Microirrigation for Onion Cultivation in a Canal Command Area - Kumar, Satyendra; Kumar, Ashwani; Singh, Rajbir (Journal of Agricultural Engineering, 2007)
Two-year field studies were carried out to determine the impact of an irrigation system comprising a secondary reservoir and pressurized (microsprinkler and drip) irrigation method in a canal irrigated area. It was hypothesized that such a system with appropriate irrigation schedule would facilitate vegetable cultivation, which requires frequent watering. The experimental crop was onion, which was irrigated through microsprinkler and drip irrigation method at irrigation schedules of 0.60; 0.80; 1.00 and 1.20 of pan evaporation (Ep). Results of the study revealed that using this system, onion production was more profitable as compared to existing irrigation practice. Between the two, microsprinkler had a better economics than drip. This conclusion is, however, dependent upon market price of onion, as with price Rs. 1.50/kg or lower, the system may become unprofitable.